Profit, Porn, and Protease Inhibitors: Ronnie Burk’s Radical Activism in “Post-AIDS” San Francisco - Victoria Carroll (European Journal of American Studies)
In early 2000 gay Latino poet Ronnie Burk courted controversy when he posted a quasi-pornographic activist flyer depicting the Executive Director of the San Francisco AIDS Foundation masturbating with a dildo inscribed with AZT on the website of the controversial San Francisco-based offshoot of the AIDS Coalition to Unleash Power. A demonstration against the commodification of HIV/AIDS and its newly emerging treatments, the image indexed the shifting responses to the epidemic in San Francisco at the beginning of the twenty-first century. This article considers the build-up and fallout attending this controversy, offering close readings of Burk’s flyer and tracing the image back to its roots in European political pornography, breaking with consensus-based HIV/AIDS discourse that curtails the narration of the epidemic in 1996, the year that the efficacy of Highly Active Antiretroviral Therapy using protease inhibitors was confirmed.